Why is the antipodal effect in closo-1-SB9H9 so large? A possible explanation based on the geometry from the concerted use of gas electron diffraction and computational methods - Hnyk, Drahomír; Wann, Derek A; Holub, Josef; Samdal, Svein; Rankin, David W H (Dalton transactions (Cambridge, England, 2011)
The molecular structure of 1-thia-closo-decaborane(9), 1-SB(9)H(9), has been determined by the concerted use of gas electron diffraction and quantum-chemical calculations. Assuming C(4v) symmetry, the cage structure was distorted from a symmetrically bicapped square antiprism (D(4d) symmetry) mainly through substantial expansion of the tetragonal belt of boron atoms adjacent to sulfur. The S-B and (B-B)(mean) distances are well determined with r(h1) = 193.86(14) and 182.14(8) pm, respectively. Geometrical parameters calculated using the MP2(full)/6-311++G** method and at levels reported earlier [MP2(full)/6-311G**, B3LYP/6-311G** and B3LYP/cc-pVQZ], as well as calculated vibrational amplitudes and (11)B NMR chemical shifts, are in good agreement with the experimental findings. In particular, the so-called antipodal chemical shift of apical B(10) (71.8 ppm) is reproduced well by the GIAO-MP2 calculations and its large magnitude is schematically accounted for, as is the analogous antipodal chemical shift of B(12) in the twelve-vertex closo-1-SB(11)H(11).